2014
DOI: 10.1590/1809-6891v15i219521
|View full text |Cite
|
Sign up to set email alerts
|

Effluents quality during the grow-out phase of the amazon shrimp macrobrachium amazonicum

Abstract: In recent years shrimp culture farms have been one of the most growing sectors in aquaculture. Research has been carried out in order to establish a sustainable production maintaining profit and low environmental impact. Current investigation analyzed source and effluent water produced during the final grow-out phase of the Amazon shrimp (Macrobrachium amazonicum). Twelve natural-bottom ponds, with continuous water flow and stock density comprising 40, 60, 80 and 100 young shrimps/m² were analyzed. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this study, we observed increases in density contributed to increases in nitrogen compounds especialy nitrate (NO 3− N). However, the total ammonia data and nitrite observed in this trial below the suggested values for the M. amazonicum cultivation Valenti 2007, 2010;Nogueira et al 2014, Zou et al 2016. Between nitrogen compounds, NO 3 -N is the end product of nitrification and also the main nutrient for plant growth in aquaponics, and thus concentration observed in the water is the equilibrium result between nitrification and plant absorption (Zou et al 2016).…”
Section: Water Quality and Growth Of Hydroponic Cropsmentioning
confidence: 51%
See 1 more Smart Citation
“…In this study, we observed increases in density contributed to increases in nitrogen compounds especialy nitrate (NO 3− N). However, the total ammonia data and nitrite observed in this trial below the suggested values for the M. amazonicum cultivation Valenti 2007, 2010;Nogueira et al 2014, Zou et al 2016. Between nitrogen compounds, NO 3 -N is the end product of nitrification and also the main nutrient for plant growth in aquaponics, and thus concentration observed in the water is the equilibrium result between nitrification and plant absorption (Zou et al 2016).…”
Section: Water Quality and Growth Of Hydroponic Cropsmentioning
confidence: 51%
“…But in phosphate, it possibly caused the increase of this parameter especially in the treatment with 120 shrimps, where the pH value was lower as observed by Cerozi and Fitzsimmons (2016) that recommended pH in aquaponics systems at a 5.5-7.2 range for optimal availability and uptake by plants. However, phospate and nitrogen compound (ammonia, nitrite, and nitrate) concentrations are related to the addition of feed in the Macrobrachium amazonicum culture tanks, which generate many organic wastes (non-consumed feed, feces, and others) in the sediment (Nogueira et al 2014).…”
Section: Water Quality and Growth Of Hydroponic Cropsmentioning
confidence: 99%